(untitled) (ACME, 2020)
For the first time the director Ariane Mnouchkine, founder of the Théâtre du Soleil in the 1960s, left the direction of a show by her theater company to another artist. He is the award-winning director and actor Robert Lepage, born in Québec city. The show tells the story of Indian natives in Canada but immediately before the premiére, the story takes on the tones of a cultural controversy. Mnouchkine and Lepage are accused of “cultural appropriation”: who has the right to tell the dramatic stories of the “First Nations” populations? Why the dominant culture should be the spokesman for a minority culture? Beyond the story, the show focuses on the critical reflection on the role of the theater in society nowadays.